A rare case of ivory osteoma of mastoid bone - Maingi, Sahil; Jain, Shalini; Rai, A. K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Osteomas are benign slow-growing bony tumour predominantly occurring in long bones, rarely found in the skull. In the skull they are found most commonly in fronto-ethmoid region. They are very rarely found in the temporal bone. They are usually asymptomatic and treated mainly for cosmetic purposes. We describe a case of a 33 years old female presented to us with right sided mastoid swelling from last 6 years.